Preparation process of ultra-high temperature rolled molybdenum alloy

CN118147504BActive Publication Date: 2026-10-30HENAN UNIV OF SCI & TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410278159.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-12
Publication Date
2026-10-30
Estimated Expiration
2044-03-12

AI Technical Summary

Technical Problem

[0003]纳米陶瓷是将纳米级陶瓷颗粒、晶须、纤维等引入陶瓷母体,以改善陶瓷的性能而制造的复合型材料,其提高母体材料的室温力学性能,改善高温性能,并且此材料具有可切削加工和超塑性;纳米陶瓷的特性主要在于力学性能方面,包括纳米陶瓷材料的硬度、断裂韧度和低温延展性等,使用纳米陶瓷颗粒强化合金复合材料的力学性能是一种有效的技术手段;目前,进一步加强钼合金性能通常依赖于增加纳米陶瓷颗粒的体积分数或引入更硬的金属间化合物,但在钼合金的高温制备过程中,加入纳米陶瓷颗粒实现钼合金高强度的同时,也不可避免地会降低其延展性和高温稳定性

Benefits of technology

[0020](1)本发明提供了一种超高温轧制钼合金的制备工艺,将氧化物与苯磺酸混合溶液超声分散均匀,经水热反应后得到磺酸基改性的氧化物(MOx-SO3H+),加入可溶性钼盐形成(MOx-SO3H)2-MoO4;再用酸调控pH值、经水热、氢还原得到粒度为0.5-5μm的纳米陶瓷氧化物增强钼合金粉体;本发明实现了氧化物与钼原子级混合,解决了传统球磨工艺制备陶瓷相强化钼合金造成的混粉不均匀的问题,且本发明制备方法简单且操作性强,易实现大规模生产。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118147504B_ABST
    Figure CN118147504B_ABST
Patent Text Reader

Abstract

The application provides a preparation process of ultrahigh-temperature rolled molybdenum alloy, which comprises the following steps: uniformly ultrasonic dispersing oxides and a mixed solution of benzenesulfonic acid to obtain sulfonic acid group modified oxides (MOx-SO3H + ) through a hydrothermal reaction; adding soluble molybdenum salt to form (MOx-SO3H)2-MoO4; adjusting the pH value through acid and obtaining nano ceramic oxide reinforced molybdenum alloy powder with a particle size of 0.5-5 μm through a hydrothermal reaction and hydrogen reduction; the application realizes atomic-level mixing of oxides and molybdenum, solves the problem of uneven mixing of powder caused by traditional ball milling process for preparing ceramic phase reinforced molybdenum alloy; the prepared ultrahigh-strength and high-toughness molybdenum alloy has more superior overall performance, can simultaneously have good tensile strength and elongation, can keep stable at a high-temperature environment of 1500 DEG C, meets the application conditions of the ultrahigh-temperature environment, and can be used as a high-temperature refractory structural component material; and the preparation method is simple, has strong operability, and is easy to realize large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of alloy materials technology, specifically relating to a preparation process for ultra-high temperature rolled molybdenum alloy. Background Technology

[0002] Molybdenum alloys possess characteristics such as high melting point, high high-temperature strength, low high-temperature creep rate, good thermal and electrical conductivity, small coefficient of expansion, good thermal shock resistance, and strong corrosion resistance. They are widely used in the chemical, metallurgical, metal processing, aerospace, and nuclear energy industries. In high-temperature applications, molybdenum alloys have irreplaceable advantages, such as in high-temperature components in aerospace turbine engines, missiles in the military industry, and fusion reactors in the nuclear industry, as well as high-temperature nozzles in aero engines and molybdenum mandrels in the metallurgical industry. Furthermore, due to their suitable density and low neutron absorption cross-section, molybdenum alloys are the only ideal material for the core of high-temperature space nuclear reactors. High-temperature structural components have extremely high requirements for material safety and reliability, specifically reflected in high recrystallization temperatures and excellent strength and ductility at both room temperature and high temperatures.

[0003] Nanoceramics are composite materials manufactured by introducing nano-sized ceramic particles, whiskers, fibers, etc., into a ceramic matrix to improve its properties. They enhance the room temperature mechanical properties and high-temperature performance of the matrix material, and also possess machinability and superplasticity. The main characteristics of nanoceramics lie in their mechanical properties, including hardness, fracture toughness, and low-temperature ductility. Using nanoceramic particles to strengthen the mechanical properties of alloy composites is an effective technical means. Currently, further enhancing the properties of molybdenum alloys usually relies on increasing the volume fraction of nanoceramic particles or introducing harder intermetallic compounds. However, in the high-temperature preparation process of molybdenum alloys, while adding nanoceramic particles achieves high strength, it inevitably reduces its ductility and high-temperature stability.

[0004] In addition, the rolling temperature is generally chosen to be close to the recrystallization temperature; the rolling temperature of pure Mo using common technology is 1100℃, and the rolling temperature of two-phase doped Mo alloys such as TZM, Mo-La2O3 and Mo-ZrC is 1350℃; if the rolling temperature is too low, the slab will be hard and cracks will occur during the rolling process, making it impossible to obtain a complete slab and causing the product dimensions to not meet the requirements; if the rolling temperature is too high, the slab will crack and rolling will not be possible. The selection of rolling temperature also plays a crucial role in thermoplastic deformation. Summary of the Invention

[0005] To address the problems existing in the prior art, this invention proposes a preparation process for ultra-high temperature rolled molybdenum alloys. The aim is to achieve effective control over the size, distribution, crystal form, and interface structure of nano-ceramic particles through an integrated liquid-liquid doping, co-precipitation, and co-decomposition process. This significantly improves the density and recrystallization temperature of the sintered molybdenum alloy, and weakens the molybdenum alloy through ultra-high temperature rolling. <110> By employing directional texturing, an ultra-high strength and toughness molybdenum alloy with excellent mechanical properties and high-temperature stability was prepared.

[0006] The ultra-high strength and toughness molybdenum alloy prepared by the ultra-high temperature rolled molybdenum alloy of this invention comprises: 95wt%-99.9wt% molybdenum and 0.1wt%-5wt% nano-ceramic oxide particles; the preparation process of the ultra-high temperature rolled molybdenum alloy of this invention specifically includes the following steps:

[0007] (1) Preparation of aqueous solution of MOx-SO3H: Benzenesulfonic acid and nano-ceramic oxide particles with a particle size of 10-200nm are uniformly mixed in water, and then subjected to hydrothermal reaction to obtain an aqueous solution of sulfonic acid modified oxide (MOx-SO3H).

[0008] (2) Preparation of precursor composite powder: Prepare an aqueous solution of molybdenum salt with a concentration of 0.02-2.5 mol / L, and add it to an aqueous solution of MOx-SO3H to obtain a mixed solution. Add lactic acid to the mixed solution to make the pH reach 5.5-6.5, and then stir, dry and pulverize to obtain the precursor composite powder.

[0009] (3) Preparation of molybdenum alloy powder reinforced with nano-ceramic oxide by reduction: The obtained precursor composite powder is reduced in hydrogen in two stages to obtain molybdenum alloy powder reinforced with nano-ceramic oxide with a particle size of 0.5-5μm.

[0010] (4) Preparation of ultra-high strength and toughness molybdenum alloy by pressing and sintering: After pressing the molybdenum alloy powder reinforced with nano-ceramic oxide, it is sintered in a hydrogen atmosphere to obtain a molybdenum alloy reinforced with nano-ceramic oxide with a density greater than 98%. The molybdenum alloy reinforced with nano-ceramic oxide is rolled at ultra-high temperature to obtain an ultra-high strength and toughness molybdenum alloy.

[0011] Specifically, the nano-ceramic oxide particles in step (1) are one of zirconium oxide, titanium oxide, aluminum oxide, hafnium oxide, yttrium oxide, and lanthanum oxide;

[0012] Specifically, in step (1), the hydrothermal reaction temperature is 60-90℃, the reaction time is 2-8h, and the stirring rate is 50-300r / min;

[0013] Specifically, the molybdenum salt used in step (2) is one or more of potassium molybdate, sodium molybdate, and ammonium molybdate.

[0014] Specifically, in step (3), the first stage of reduction is heated to 350-550℃, and the hydrogen flow rate is 15-18m³. 3 The temperature is maintained at 18-25 m³ / h for 4-9 hours; the second stage of reduction involves raising the temperature to 800-950℃ and using a hydrogen flow rate of 18-25 m³ / h. 3 / h, keep warm for 8-12h;

[0015] Specifically, in step (4), a cold isostatic press is used for powder pressing, with a pressure of 150-200 MPa and a holding time of 15-20 min.

[0016] Specifically, in step (4), a pressureless medium-frequency furnace is used for sintering, with a sintering temperature of 1700-2000℃, a holding time of 4-10h, and a hydrogen flow rate of 18-25m³ / h. 3 / h;

[0017] Specifically, in step (4), the rolling temperature is 1500-1700℃, one pass per rolling pass, the deformation per pass is 30-50%, and the total deformation is >90%.

[0018] The aforementioned preparation process for ultra-high strength and toughness molybdenum alloys can also be used to prepare high-density energetic alloys such as tungsten alloys and tungsten-nickel-iron alloys.

[0019] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0020] (1) This invention provides a process for preparing ultra-high temperature rolled molybdenum alloy, wherein an oxide and a benzenesulfonic acid mixed solution are ultrasonically dispersed evenly, and a sulfonic acid-modified oxide (MOx-SO3H) is obtained after hydrothermal reaction. + A soluble molybdenum salt is added to form (MOx-SO3H)2-MoO4; then the pH value is adjusted with acid, and the mixture is subjected to hydrothermal treatment and hydrogen reduction to obtain nano-ceramic oxide-reinforced molybdenum alloy powder with a particle size of 0.5-5μm. This invention achieves atomic-level mixing of oxide and molybdenum, solving the problem of uneven powder mixing caused by traditional ball milling process in preparing ceramic phase-reinforced molybdenum alloys. Moreover, the preparation method of this invention is simple, easy to operate, and can be easily mass-produced.

[0021] (2) The preparation conditions of this invention are controllable. By adjusting the pressing and sintering process conditions of the molybdenum alloy, the density (density greater than 98%) and recrystallization temperature (recrystallization temperature reaches above 1500℃) of the sintered molybdenum alloy are improved, thereby ensuring the smooth progress of subsequent high-temperature rolling. Among them, adjusting the sintering process ensures that most of the nano-sized oxides are dispersed inside the grains and that as few as possible are segregated on the grain boundaries, thus ensuring the toughness of the molybdenum alloy. Preparing fine grains increases the grain boundary and enhances the strengthening effect. More grain boundaries and nano-oxides hinder dislocation movement, thereby achieving a significant increase in recrystallization temperature and ensuring that the alloy meets the basic requirements for ultra-high temperature rolling. Increasing the density prevents the alloy from cracking during the subsequent high-temperature rolling process.

[0022] (3) Reasons for the poor toughness of molybdenum plates prepared by traditional processes: parallel to <111> The particles on the rolling surface have a high solubility for interstitial atoms, which causes many impurities to tend towards... <111> The rolling surface greatly affects the parallel to <111> Surface adhesion energy of particles on rolling surfaces; poor transverse plasticity of Mo alloys and <110> The structure is closely related, because <110> The structure leads to large transverse grains, and impurity elements tend to be concentrated at grain boundaries, resulting in a significant reduction in interfacial bonding strength and poor transverse plasticity of the alloy. Therefore, this invention employs an ultra-high rolling start temperature to achieve a large single-pass deformation of the molybdenum alloy, rolling it to the core in one pass to ensure consistent performance across all parts of the slab. Repeated ultra-high temperature annealing weakens the slab texture, avoiding the formation of strong matrix surface textures during the rolling process that lead to poor room-temperature performance. Recrystallization is an effective method for weakening the matrix structure. This invention generates fine, near-spherical grains after recrystallization nucleation, achieving ultra-high toughness in the slab and avoiding slab cracking during the rolling process.

[0023] (4) The ultra-high strength and toughness molybdenum alloy prepared by this invention has superior overall performance, simultaneously achieving good tensile strength and elongation: at room temperature, the tensile strength can reach over 600 MPa and the elongation can reach over 50%, which is more than 35% higher than the tensile strength and more than 100% higher than the traditional molybdenum alloy; at a high temperature of 1200℃, the tensile strength can reach over 230 MPa and the elongation can reach over 30%, which is more than 50% higher than the tensile strength and more than 80% higher than the traditional molybdenum alloy, respectively. The ultra-high strength and toughness molybdenum alloy finally prepared by this invention can remain stable at a high temperature of 1500℃, meeting the application conditions of ultra-high temperature environments. It can be used as a material for high-temperature refractory structural components and is suitable for military, aerospace and other fields, with broad application prospects. Attached Figure Description

[0024] Figure 1 The morphology and pole figure of the ultra-high strength and toughness molybdenum alloy obtained in Example 1 of the present invention are shown.

[0025] Figure 2 The morphology and pole figure of the ultra-high strength and toughness molybdenum alloy obtained in Example 2 of the present invention are shown.

[0026] Figure 3 The morphology and pole figure of the ultra-high strength and toughness molybdenum alloy obtained in Example 3 of the present invention are shown.

[0027] Figure 4 Morphology and pole figure of pure molybdenum prepared for Comparative Example 1;

[0028] Figure 5 Morphology and pole figure of the ultra-high strength and toughness molybdenum alloy prepared for Comparative Example 2;

[0029] Figure 6 The figures show the room temperature stress-strain curves for Examples 1-3 and Comparative Examples 1-2. Detailed Implementation

[0030] To better understand the content of this invention, the invention will be further described below with reference to specific embodiments and accompanying drawings. The following embodiments are based on the technology of this invention and provide detailed implementation methods and operating steps, but the scope of protection of this invention is not limited to the following embodiments.

[0031] Example 1

[0032] (1) Benzenesulfonic acid and nano-zirconia ceramic particles with a particle size of 50 nm were uniformly mixed in water, and then subjected to a hydrothermal reaction at 90 °C for 6 h. After stirring, an aqueous solution of MOx-SO3H was obtained.

[0033] (2) A 1.0 mol / L aqueous solution of molybdate was prepared using potassium molybdate and added to an aqueous solution of MOx-SO3H to obtain a mixed solution. Lactic acid was added to the mixed solution to make the pH reach 6.0. The precursor composite powder was then obtained by stirring, drying and pulverizing.

[0034] (3) The obtained precursor composite powder was reduced in hydrogen in two stages. The first stage of reduction was heated to 550℃ and the hydrogen flow rate was 17m³ / h. 3 / h, hold at this temperature for 8 hours; the second stage of reduction is heated to 925℃ with a hydrogen flow rate of 22m³ / h. 3 / h, heat preservation for 10h; after reduction, molybdenum alloy powder reinforced with nano-zirconia ceramic particles with a particle size of 0.7μm is obtained;

[0035] (4) The molybdenum alloy powder reinforced with nano-zirconia ceramic particles was pressed in a cold isostatic press at 180 MPa for 20 min, and then sintered in a pressureless medium-frequency furnace at 1960℃ with a hydrogen flow rate of 20 m³ / min. 3 After holding at this temperature for 6 hours, a molybdenum alloy reinforced with nano-zirconia ceramic particles with a density of 98.5% was obtained.

[0036] (5) The molybdenum alloy reinforced with nano-zirconia ceramic particles was rolled at 1550℃ to obtain an ultra-high strength and toughness molybdenum alloy. The single-pass deformation was 42%, and the total deformation was 97.8% after 7 passes of rolling.

[0037] The ultra-high strength and toughness molybdenum alloy prepared by ultra-high temperature rolling process in Example 1 comprises 99 wt% molybdenum and 1 wt% nano-zirconia ceramic particles. The ultra-high strength and toughness molybdenum alloy exhibits a tensile strength of 737 MPa and an elongation of 53%, representing increases of 82.9% in tensile strength and 89.3% in elongation compared to traditional molybdenum alloys. It also demonstrates high-temperature stability and a texture strength of 2.98. Specifically... Figure 1 As shown.

[0038] Example 2

[0039] (1) Benzenesulfonic acid and nano-alumina ceramic particles with a particle size of 20 nm were uniformly mixed in water, and then subjected to a hydrothermal reaction at 70 °C for 8 h. After stirring, an aqueous solution of MOx-SO3H was obtained.

[0040] (2) Prepare a 1.5 mol / L sodium molybdate aqueous solution and add it to an aqueous solution of MOx-SO3H to obtain a mixed solution. Add lactic acid to the mixed solution to make the pH reach 5.5. Then, after stirring, drying and pulverizing, the precursor composite powder is obtained.

[0041] (3) The obtained precursor composite powder was reduced in hydrogen in two stages. The first stage of reduction was heated to 500℃ and the hydrogen flow rate was 18m³ / h. 3 / h, hold at this temperature for 6h; the second stage of reduction is heated to 850℃, with a hydrogen flow rate of 25m³ / h. 3 / h, heat preservation for 12h; after reduction, molybdenum alloy powder reinforced with nano-alumina ceramic particles with a particle size of 0.8μm was obtained;

[0042] (4) The molybdenum alloy powder reinforced with nano-alumina ceramic particles was pressed in a cold isostatic press at 200 MPa for 15 min, and then sintered in a pressureless medium-frequency furnace at 1850℃ with a hydrogen flow rate of 25 m³ / min. 3 After holding at this temperature for 7 hours, a molybdenum alloy reinforced with nano-alumina ceramic particles with a density of 98.8% was obtained.

[0043] (5) The molybdenum alloy reinforced with nano-alumina ceramic particles was rolled at 1600℃ to obtain an ultra-high strength and toughness molybdenum alloy. The single-pass deformation was 47%, and the total deformation was 95.82% after 5 passes of rolling.

[0044] The ultra-high strength and toughness molybdenum alloy prepared by ultra-high temperature rolling process in Example 2 comprises 99.5 wt% molybdenum and 0.5 wt% nano-alumina ceramic particles. The ultra-high strength and toughness molybdenum alloy exhibits a tensile strength of 856 MPa and an elongation of 58.1%, representing increases of 112.4% in tensile strength and 107.1% in elongation compared to traditional molybdenum alloys. It also demonstrates high-temperature stability and a texture strength of 2.82. Specifically... Figure 2 As shown.

[0045] Example 3

[0046] (1) Benzenesulfonic acid and nano-titanium oxide ceramic particles with a particle size of 100 nm were uniformly mixed in water, and then subjected to a hydrothermal reaction at 75 °C for 8 h. After stirring, an aqueous solution of MOx-SO3H was obtained.

[0047] (2) Prepare a 2.5 mol / L molybdate aqueous solution and add it to the MOx-SO3H aqueous solution to obtain a mixed solution. Add lactic acid to the mixed solution to make the pH reach 6.5. Then, after stirring, drying and pulverizing, the precursor composite powder is obtained.

[0048] (3) The obtained precursor composite powder was reduced in hydrogen in two stages. The first stage of reduction was heated to 450℃ and the hydrogen flow rate was 15m³ / h. 3 / h, hold at this temperature for 9h; the second stage of reduction is heated to 800℃, with a hydrogen flow rate of 25m³ / h. 3 / h, heat preservation for 12h; after reduction, molybdenum alloy powder reinforced with nano-titanium oxide ceramic particles with a particle size of 0.5μm is obtained;

[0049] (4) The molybdenum alloy powder reinforced with nano-titanium oxide ceramic particles was pressed in a cold isostatic press at 190 MPa for 18 min, and then sintered in a pressureless medium-frequency furnace at 1750℃ with a hydrogen flow rate of 23 m³ / min. 3 After holding at this temperature for 10 hours, a molybdenum alloy reinforced with nano-titanium oxide ceramic particles with a density of 98.9% was obtained.

[0050] (5) The molybdenum alloy reinforced with nano-titanium oxide ceramic particles was rolled at 1600℃ to obtain an ultra-high strength and toughness molybdenum alloy. The rolling process was carried out in one pass, with a single deformation of 35%. The total deformation was 97.9% after 9 passes.

[0051] The ultra-high strength and toughness molybdenum alloy prepared by ultra-high temperature rolling process in Example 3 comprises 98.5 wt% molybdenum and 1.5 wt% nano-titanium oxide ceramic particles. The ultra-high strength and toughness molybdenum alloy exhibits a tensile strength of 864 MPa and an elongation of 63%, representing increases of 114.4% in tensile strength and 125% in elongation compared to traditional molybdenum alloys, respectively. It also demonstrates high-temperature stability and a texture strength of 2.31. Specifically... Figure 3 As shown.

[0052] Comparative Example 1

[0053] (1) Ammonium tetramolybdate was reduced in two stages in hydrogen gas. The first stage of reduction was carried out at a temperature of 550°C with a hydrogen flow rate of 18 m³ / s. 3 / h, hold at this temperature for 8 hours; the second stage of reduction is heated to 950℃, with a hydrogen flow rate of 25m³ / h. 3 / h, heat preservation for 10h; after reduction, molybdenum powder with a particle size of 3.5μm was obtained;

[0054] (2) The molybdenum powder was pressed in a cold isostatic press at 200 MPa for 20 min, and then sintered in a pressureless medium-frequency furnace at 1960℃ with a hydrogen flow rate of 20 m³ / min. 3 / h, after holding at this temperature for 10h, pure molybdenum with a density of 95.6% was obtained.

[0055] (3) Pure molybdenum is rolled at 1100℃, one pass per heat, with a single deformation of 28%, and 9 passes per rolling, with a total deformation of 94.81%.

[0056] Comparative Example 1 yielded pure molybdenum with a tensile strength of 403 MPa, an elongation of 28%, and a texture strength of 11.79. (Specific details are as follows...) Figure 4 As shown.

[0057] Comparative Example 2

[0058] (1) Using a solid-solid mixing method, 100nm nano-titanium oxide ceramic particles and ammonium tetramolybdate are mixed in a dual-power mixer at a speed of 50r / min for 6h to obtain precursor composite powder.

[0059] (2) The obtained precursor composite powder was reduced in hydrogen in two stages. The first stage of reduction was heated to 450℃ and the hydrogen flow rate was 15m³ / h. 3 / h, hold at this temperature for 9h; the second stage of reduction is heated to 800℃, with a hydrogen flow rate of 25m³ / h. 3 / h, heat preservation for 12h; after reduction, molybdenum alloy powder reinforced with nano-titanium oxide ceramic particles with a particle size of 1.5μm is obtained;

[0060] (4) The molybdenum alloy powder reinforced with nano-titanium oxide ceramic particles was pressed in a cold isostatic press at 190 MPa for 18 min, and then sintered in a pressureless medium-frequency furnace at 1750℃ with a hydrogen flow rate of 23 m³ / min. 3 After holding at this temperature for 10 hours, a molybdenum alloy reinforced with nano-titanium oxide ceramic particles with a density of 97.7% was obtained.

[0061] (5) The molybdenum alloy reinforced with nano-titanium oxide ceramic particles was rolled at 1600℃ to obtain an ultra-high strength and toughness molybdenum alloy. The rolling process was carried out in one pass, with a single deformation of 35%. The total deformation was 97.9% after 9 passes.

[0062] Comparative Example 2 describes an ultra-high strength and toughness molybdenum alloy prepared using an ultra-high temperature rolling process. The alloy comprises 98.5 wt% molybdenum and 1.5 wt% nano-titanium oxide ceramic particles. The tensile strength of this ultra-high strength and toughness molybdenum alloy reaches 700 MPa, and the elongation reaches 26%, representing a 73.7% increase in tensile strength and a 7.1% decrease in elongation compared to traditional molybdenum alloys. The texture strength is 6.52. (Specific details are as follows...) Figure 5 As shown.

[0063] In summary, please refer to Figure 6 It can be concluded that the ultra-high strength and toughness molybdenum alloy prepared by the present invention has superior overall performance, and its toughness is also greatly improved while maintaining high strength at room temperature.

[0064] The above description is merely a preferred embodiment of the present invention. The present invention may have other embodiments based on the above preparation method, which will not be listed hereafter. Therefore, any simple modifications, equivalent changes, and alterations made by those skilled in the art to the above embodiments without departing from the scope of the present invention's technical solution, based on the technical essence of the present invention, shall still fall within the scope of the present invention's technical solution.

Claims

1. A preparation process for ultra-high temperature rolled molybdenum alloy, characterized in that, Specifically, the following steps are included: (1) Preparation of an aqueous solution of MOx-SO3H: Benzenesulfonic acid and nano-ceramic oxide particles with a particle size of 10-200 nm are uniformly mixed in water, and then subjected to hydrothermal reaction to obtain an aqueous solution of MOx-SO3H; the nano-ceramic oxide particles are one of zirconium oxide, titanium oxide, aluminum oxide, hafnium oxide, yttrium oxide, and lanthanum oxide. (2) Preparation of precursor composite powder: Prepare an aqueous solution of molybdenum salt with a concentration of 0.02-2.5 mol / L and add it to an aqueous solution of MOx-SO3H to obtain a mixed solution. Add lactic acid to the mixed solution to make the pH reach 5.5-6.

5. Then, after stirring, drying and pulverizing, the precursor composite powder is obtained. (3) Preparation of molybdenum alloy powder reinforced with nano-ceramic oxide by reduction: The obtained precursor composite powder is reduced in hydrogen in two stages to obtain molybdenum alloy powder reinforced with nano-ceramic oxide with a particle size of 0.5-5μm. (4) Pressing and sintering to prepare ultra-high strength and toughness molybdenum alloy: After pressing the molybdenum alloy powder reinforced with nano-ceramic oxide, it is sintered in a hydrogen atmosphere to obtain a molybdenum alloy reinforced with nano-ceramic oxide with a density greater than 98%. The molybdenum alloy reinforced with nano-ceramic oxide is rolled at ultra-high temperature to obtain an ultra-high strength and toughness molybdenum alloy. Powder pressing is performed using a cold isostatic press with a pressure of 150-200 MPa and a holding time of 15-20 min. Sintering was carried out in a pressureless medium-frequency furnace at a temperature of 1700-2000℃, a holding time of 4-10 h, and a hydrogen flow rate of 18-25 m³ / h. 3 / h; the rolling temperature is 1500-1700℃, one pass and one heat, the deformation per pass is 30-50%, and the total deformation is >90%; the ultra-high strength and toughness molybdenum alloy obtained includes: 95 wt%-99.9 wt% molybdenum and 0.1 wt%-5 wt% nano-ceramic oxide particles.

2. The preparation process of an ultra-high temperature rolled molybdenum alloy as described in claim 1, characterized in that, The hydrothermal reaction temperature in step (1) is 60-90℃, the reaction time is 2-8 h, and the stirring rate is 50-300 r / min.

3. The preparation process of an ultra-high temperature rolled molybdenum alloy as described in claim 1, characterized in that, The molybdenum salt used in step (2) is one or more of potassium molybdate, sodium molybdate, and ammonium molybdate.

4. The preparation process of an ultra-high temperature rolled molybdenum alloy as described in claim 1, characterized in that, In step (3), the first stage of reduction is heated to 350-550℃, and the hydrogen flow rate is 15-18 m³ / h. 3 The temperature is maintained at 18-25 m³ / h for 4-9 hours; the second stage of reduction involves raising the temperature to 800-950℃ and using a hydrogen flow rate of 18-25 m³ / h. 3 / h, keep warm for 8-12 h.

5. The preparation process of an ultra-high temperature rolled molybdenum alloy as described in claim 1, characterized in that, The ultra-high strength and toughness molybdenum alloy has a tensile strength of over 600 MPa and an elongation of over 50% at room temperature, and a tensile strength of over 230 MPa and an elongation of over 30% at a high temperature of 1200℃.

Citation Information

Patent Citations

  • Method for improving mechanical property of ceramic phase reinforced molybdenum alloy

    CN115896521A